1987
DOI: 10.1002/app.1987.070330828
|View full text |Cite
|
Sign up to set email alerts
|

Reaction kinetics for hindered amine/epoxides by DSC

Abstract: SynopsisThe rate constants for the reaction of two aliphatic hindered amines with phenylglycidyl ether (PGE) and the diglycidyl ether of bisphenol A (DER 332) were determined by differential scanning calorimetry (DSC). The two exothermic peaks which are present in the DSC data result from the consecutive reactions of the primary and secondary amine hydrogens and allow k , and k , to be determined. The resulting k,/k, ratios obtained for these hindered amine systems are larger than the ratios previously reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…They proposed that polyamide has a relatively better affinity for the silicate surface than the alkyl part of the organoclay. Thus, minimizing the number of alkyl tails maximizes the platelet dispersion in this polar polymer 33. The XRD and TEM data in our study lead to similar conclusions for the binary and ternary nanocomposites.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…They proposed that polyamide has a relatively better affinity for the silicate surface than the alkyl part of the organoclay. Thus, minimizing the number of alkyl tails maximizes the platelet dispersion in this polar polymer 33. The XRD and TEM data in our study lead to similar conclusions for the binary and ternary nanocomposites.…”
Section: Resultssupporting
confidence: 82%
“…In addition, unless there is a large affinity between the matrix and organoclay, some organoclay particles might be located at the interphase, resulting in an increase in the domain size. Polyamide‐6 has reactive functionality through amine and carboxyl end groups that are capable of reacting with the epoxy group of the elastomer 33–36. The epoxide group can also undergo ring‐opening polymerization in the presence of acid, amine, and hydroxyl end groups.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that there are strong interactions or some reactions between the modified silica particles and PEGMA. Many studies demonstrate that amine groups are capable of reacting with epoxy groups, as shown in the following scheme: [20][21][22][23][24] …”
Section: Dispersion Of Nano-silica In Pegmamentioning
confidence: 99%
“…Amine structure also plays a factor in the overall reactivity of the primary and secondary amines. Reactivity is a function of steric factors 6,7 and amine basicity. [7][8][9][10][11][12][13] Amine reaction mechanisms using tetraglycidyl-4,4'-diaminodiphenylmethane (TGDDM) are also established in literature.…”
mentioning
confidence: 99%
“…Reactivity is a function of steric factors 6,7 and amine basicity. [7][8][9][10][11][12][13] Amine reaction mechanisms using tetraglycidyl-4,4'-diaminodiphenylmethane (TGDDM) are also established in literature. 6,[14][15][16] TGDDM reactions demonstrate that epoxide type also influences kinetics and deviates from diglycidyl ether bisphenol A (DGEBA) resins.…”
mentioning
confidence: 99%